STRATEGI PENGEMBANGAN KAMPUNG EKOLOGI BATU (KEB) BERBASIS BAURAN PEMASARAN - Saparingga, Erik; Sadiyah, Ana Arifatus; Khoirunnisa, Ninin (Fakultas Pertanian, 2019)
Developing a strategy is a development planning activities at l akukan to attract visitors. This study aims at 1) . analyze the internal and external factors of the development of the Stone Ecology Village (KEB).2) . Analyze the strategy of developing the Ecological Stone Village (KEB) in increasing tourist visits. 3) . Analyzing the development strategy is the most effective Stone Ecology Village (KEB). The sampling method uses sample techniques, namely : Purposive Sampling and Accidental Sampling. The results of this study indicate that (KEB) has used 7 P Marketing Mix on Internal KEB. The results of the IE Matrix are obtained based on the weight and rating obtained from IFE and EFE which indicate the position of the IE KEB Matrix in the Growing and Building area, which means that the KEB business is developing and has excellent potential to be able to increase tourism, and Results The most effective SWOT analysis in the study is in the S-O strategy. Strategi pengembangan merupakan suatu kegiatan perencanaan pembangunan yang di lakukan untuk dapat menarik pengunjung. Penelitian ini bertujuan 1). menganalisis faktor internal dan eksternal pengembangan Kampung Ekologi Batu (KEB). 2). Menganalisis strategi pengembangan Kampung Ekologi Batu (KEB) dalam meningkatkan kunjungan wisatawan. 3). Menganalisis strategi pengembangan apakah yang paling efektif Kampung Ekologi Batu (KEB). Metode pengambilan sampel menggunakan teknik sampel yaitu : Purposive Sampling dan Accidental Sampling. Hasil penelitian ini menunjukkan bahwa (KEB) telah menggunakan 7 P Bauran Pemasaran pada Internal KEB. Hasil dari Matriks IE yang di peroleh berdasarkan bobot dan rating yang di peroleh dari IFE dan EFE yang menunjukkan posisi Matriks IE KEB berada pada daerah Tumbuh dan Membangun yang artinya KEB usaha yang sedang berkembang dan memiliki potensi yang sangat baik unrtuk dapat meningkatkan wisatanya, dan Hasil Analisis SWOT yang paling efektif dalam penelitian ialah pada strategi S â O.